Attitude Determination System For Nano Satellite Using Extended Kalman Filter On ARM7TDMI Platform - Adam Ain, Mohd Poin Keui (2014)

(untitled)
Extended Kalman Filter (EKF) has been successfully utilized in satellites missions. However, in comparison to other attitude determination methods developed, it is one of the most computationally burdening algorithm and with the new development of using nano satellites which have limited electrical power, mass, space and usually budget, it is essential to design an Attitude Determination System (ADS) which conforms to this limitation. Therefore, in this thesis, as a computational improvement on the InnoSAT project, the RCM3400 microcontroller of the ADS is replaced with the ARM7TDMI based microprocessor to test its capability. Penapisan Kalman Lanjutan (PKL) telah digunakan dengan jayanya di dalam misi satelit. Akan tetapi, jika dibandingkan dengan kaedah penentuan kedudukan lain yang telah dihasilkan, ia adalah salah satu daripada algoritma yang memiliki komputasi yang paling berat dan dengan perkembangan terkini yang menggunakan satelit nano yang mempunyai kuasa elektrik, berat, ruang dan biasanya peruntukan yang terhad, adalah menjadi satu keutamaan untuk merekabentuk sebuah Sistem Penentuan Kedudukan (SPK) yang dapat mematuhi kekangan ini.